EKSTRAKSI MINYAK JAHE MERAH (ZINGIBER OFFICINALE) MENGGUNAKAN METODE MASERASI DENGAN PERLAKUAN AWAL MENGGUNAKAN ASPERGILLUS NIGER - Rinaldo Odianda Sinaga, Adrian
Red ginger is an industrial commodity that has a large market and potential in Indonesia. Based on its use, red ginger can be used as a food product, beverage, cooking spices and essential oil, but in Indonesia the use of ginger as a derivative product such as ginger oil is still underdeveloped. One of the problems involved in the production of oil using red ginger is its low essential oil yield. One method to increase red ginger oil yield is through delignification of red ginger rhizome.This study aims to determine the ability of ginger oil bioactivity and optimal fermentation time of Aspergillus niger on red ginger rhizome (Zingiber officinale var. Roscoe) to obtain the maximum red ginger oil yield by maceration. Ginger rhizome cleaned and sterilized using exposure to ultraviolet light for 30 minutes. Aspergillus niger inoculum as much as 105 spores/g of red ginger rhizome was added to red ginger rhizome in a fermentation system. Fermentation is carried out at room temperature (25-30°C), low light intensity (~0 W/cm2), and high humidity (~99%). The fermentation time was varied for 0, 3, 6, and 9 days. Ginger oil bioactivity was tested using the Kirby-Bauer method. Red ginger oil was able to show bioactivity as an antimicrobial in the cultures of Escherichia coli and Staphylococcus aureus bacteria with inhibition zones of 0.3-0.2 cm and 0.65-0.5 cm, respectively. Measurement of lignocellulose levels was carried out using the Chesson-Datta method. The cellulose content in ginger rhizome decreased from 61.48% after fermentation for 3 days, to 57.58% after 6 days and 60.69% after 9 days. Hemicellulose content in ginger rhizome changed from 16.78% after fermentation for 3 days, to 17.03% after 6 days and 15.89% after 9 days. The lignin content in ginger rhizome changed from 19.35% after fermentation for 3 days, to 23.22% after 6 days and 21.15% after 9 days.The yield of red ginger oil from the maceration method on the 3, 6 and 9 incubation days were 1.09%, 2.27%, and 2.85% dry weight, respectively. Apart from that, the oil content of red ginger also changes during the fermentation time. The estimation of the extraction diffusion rate parameters using desorption kinetic model, mass transfer kinetic model and Lagergren’s adsorption kinetic model show the values of 1.98 × 10-12, 1.99 × 10- 12, and 2.49 × 10-12 m2/ s, respectively.